2010
DOI: 10.2174/138920110793262079
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol: A Multifunctional Cytoprotective Molecule

Abstract: Several recent studies have shown the protective effects of resveratrol in various experimental conditions and pathological animal models. Clinical studies also indicate the beneficial effects of resveratrol in different human diseases. Resveratrol produces a cascade against of events from the initial death-provoking signal, DNA fragmentation, and cell death. Researchers recognized the beneficial effect of resveratrol, as an important component, of the overall injury that occurs in various disorders such as ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 0 publications
1
26
0
2
Order By: Relevance
“…Moreover, numerous previous studies have revealed that resveratrol affects many cell biological responses such as insulin sensitivity, gluco/lipotoxicity, endoplasmic reticulum stress, oxidative stress etc., all of which contribute to diabetes, in particular type 2 diabetes [46]. Our findings here define one of the immune suppressive functions of resveratrol in protecting mice from diabetes.…”
Section: Discussionsupporting
confidence: 56%
“…Moreover, numerous previous studies have revealed that resveratrol affects many cell biological responses such as insulin sensitivity, gluco/lipotoxicity, endoplasmic reticulum stress, oxidative stress etc., all of which contribute to diabetes, in particular type 2 diabetes [46]. Our findings here define one of the immune suppressive functions of resveratrol in protecting mice from diabetes.…”
Section: Discussionsupporting
confidence: 56%
“…Understanding OSIPS in WJ-MSC is a prelude to developing protective measures against stress-induced premature senescence. Resveratrol is one of more successful drugs shown to exert such protective effects under various laboratory conditions in cell and animal models 46-48. It remains to be investigated if resveratrol exert similar desirable effects on WJ-MSC.…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, resveratrol, a naturally occurring polyphenolic compound, found predominantly in grapes and peanuts, has been widely documented in the scientific literature for its beneficial effects in preventing and/or managing several diseases [13, 14]. Over the past 6 years, we have reported potent effects of resveratrol in preventing or reversing cardiac impairment in animal models of hypertension and obesity [5, 15, 16].…”
Section: Introductionmentioning
confidence: 99%